Value of routine milking of cystic duct during laparoscopic cholecystectomy - Elbalshy, Mohammed; Gaber, Ahmed; Ammar, Mohamed S.; Soltan, Hatem (International Surgery Journal, 2017)
Background: Cystic duct stones (CDS) although they are occasionally encountered during laparoscopic cholecystectomy (LC) and are not detected easily by preoperative investigations however it is worthy to detect them intra-operatively as they will decrease the incidence of postcholecystectomy pain and they will alarm us to the more serious common bile duct (CBD) stones. So, we aimed at this study to evaluate the role of cystic duct milking in detection of cystic duct stones and its significance. Methods: This study was performed on 150 cases with calcular cholecystitis at Menofia University hospital in the period from August 2015 to May 2017. All patients had undergone LC, cystic duct milking. On table cholangiogram was done for cases that showed CDS. Results: CDS were detected in 28 cases, preoperative investigations failed to detect any of them however retrospectively 19 cases (67.8%) of them revealed to have mild transient liver functions derangement associated with acute right hypochondrial pain. Wide cystic duct (more than 4 mm) was recorded in 3 cases (10.7%) out of 28 cases that showed CDS. The incidence of association of cystic duct stones and CBD stones was found in 10 cases (35.7%). Conclusions: CDS are occasionally encountered during LC. They can be removed easily by just milking of cystic duct before clipping. The benefit is to decrease the incidence of post-cholecystectomy pain as well as it alerts us towards the more serious CBD stones. So on-table cholangiogram at that time becomes mandatory to avoid missed stone.